2020
DOI: 10.3389/fnsyn.2019.00036
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Increase of Neocortical Presynaptic Efficacy via Maturation of Vesicle Replenishment

Abstract: The efficacy of neocortical synapses to transmit during bursts of action potentials (APs) increases during development but the underlying mechanisms are largely unclear. We investigated synaptic efficacy at synapses between layer 5 pyramidal neurons (L5PNs) during development, using paired recordings, presynaptic two-photon Ca 2+ imaging, and numerical simulations. Our data confirm a developmental increase in paired-pulse ratios (PPRs). Independent of age, Ca 2+ imaging revealed no AP invasion failures and lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
9
8
0
Order By: Relevance
“…Additionally, BTBR mice display IL-NAc paired-pulse facilitation at P15 and P30 compared to C57BL/6J mice, suggesting reduced presynaptic glutamate release from IL terminals onto MSNs in BTBR mice. The difference in PPR between C57BL/6J and BTBR mice at P15 and P30 was observed using long (250 ms) and short (100 ms) interstimulus intervals, respectively, which might be influenced by developmental differences in presynaptic short-term plasticity, as reported previously [102][103][104] In the Shank3B -/mouse model of ASD, an accelerated maturation of striatal spiny projecting neurons (SPNs) of the dorsomedial striatum (DMS) was observed during early developmental stages (third and fourth postnatal weeks), followed by a decrease in corticostriatal activity during adulthood (P60) 105,106 -a deficit that was attributed to an overactivation of cortical circuits. Moreover, the authors found that increasing anterior cingulate cortex (ACC) synaptic drive to SPNs of DMS at P8 significantly increased SPN mEPSC frequency, whereas increasing ACC activity from P15 and older reduced SPN mEPSC frequency 106 , suggesting a developmental switch in the effect of cortical hyperactivity on SPN synaptic transmission.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Additionally, BTBR mice display IL-NAc paired-pulse facilitation at P15 and P30 compared to C57BL/6J mice, suggesting reduced presynaptic glutamate release from IL terminals onto MSNs in BTBR mice. The difference in PPR between C57BL/6J and BTBR mice at P15 and P30 was observed using long (250 ms) and short (100 ms) interstimulus intervals, respectively, which might be influenced by developmental differences in presynaptic short-term plasticity, as reported previously [102][103][104] In the Shank3B -/mouse model of ASD, an accelerated maturation of striatal spiny projecting neurons (SPNs) of the dorsomedial striatum (DMS) was observed during early developmental stages (third and fourth postnatal weeks), followed by a decrease in corticostriatal activity during adulthood (P60) 105,106 -a deficit that was attributed to an overactivation of cortical circuits. Moreover, the authors found that increasing anterior cingulate cortex (ACC) synaptic drive to SPNs of DMS at P8 significantly increased SPN mEPSC frequency, whereas increasing ACC activity from P15 and older reduced SPN mEPSC frequency 106 , suggesting a developmental switch in the effect of cortical hyperactivity on SPN synaptic transmission.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, BTBR mice display IL-NAc paired-pulse facilitation at P15 and P30 compared to C57BL/6J mice, suggesting reduced presynaptic glutamate release from IL terminals onto MSNs in BTBR mice. The difference in PPR between C57BL/6J and BTBR mice at P15 and P30 was observed using long (250 ms) and short (100 ms) interstimulus intervals, respectively, which might be influenced by developmental differences in presynaptic short-term plasticity, as reported previously 102104…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, BTBR mice display IL-NAc paired-pulse facilitation at P15 and P30 compared to C57BL/6J mice, suggesting reduced presynaptic glutamate release from IL terminals onto MSNs in BTBR mice. The difference in PPR between C57BL/6J and BTBR mice at P15 and P30 was observed using long (250 ms) and short (100 ms) interstimulus intervals, respectively, which might be in uenced by developmental differences in presynaptic short-term plasticity, as reported previously [102][103][104] In the Shank3B -/mouse model of ASD, an accelerated maturation of striatal spiny projecting neurons (SPNs) of the dorsomedial striatum (DMS) was observed during early developmental stages (third and fourth postnatal weeks), followed by a decrease in corticostriatal activity during adulthood (P60) 105,106a de cit that was attributed to an overactivation of cortical circuits. Moreover, the authors found that increasing anterior cingulate cortex (ACC) synaptic drive to SPNs of DMS at P8 signi cantly increased SPN mEPSC frequency, whereas increasing ACC activity from P15 and older reduced SPN mEPSC frequency 106 , suggesting a developmental switch in the effect of cortical hyperactivity on SPN synaptic transmission.…”
Section: Discussionsupporting
confidence: 75%
“…2020; Bornschein et al . 2020). In the model without SV replenishment of the docking sites, the cumulative plot (filled squares) stayed along the parabola fitting the standard variance‐mean plot (open circles; Fig.…”
Section: Resultsmentioning
confidence: 99%